Renal surgery in the dog and cat - PAPAZOGLOU (Λ.Γ. ΠΑΠΑΖΟΓΛΟΥ), L. G.; KOUTI (Β. ΚΟΥΤΗ), V. (Journal of the Hellenic Veterinary Medical Society, 2017)
Nephrectomy is the complete removal of the kidney and ipsilateral ureter and usually it is performed through a midline laparotomy for the treatment of end stage unilateral kidney disease. Indications for performing nephrectomy may include: renal and ureteral neoplasms, persistent renal haematuria, serious renal trauma associated with or without avulsion of renal pedicle, end-stage hydronephrosis, single renal cysts associated with renal disease, polycystic kidney disease associated with pyelonephritis, renal parasites, renal or perirenal abscessation, chronic end-stage pyelonephritis and renal disease associated with ectopic ureter. Normal function of the contralateral kidney is a prerequisite for performing nephrectomy. The presence of azotaemia or persistent isosthenuria is a contraindication for nephrectomy. Nephrectomy for pyelonephritis may not consistently resolve the infection in the remaining kidney. Preoperative evaluation of renal function in animals undergoing nephrectomy would ideally include determination of glomerular filtration rate using renal nuclear scintigraphy. However, in clinical practice, excretory urography is performed for the assessment of renal function. Nephrotomy is a limited surgical incision through the dorsal renal surface to remove nephroliths, to explore the pelvis for polyps and neoplasms and to identify causes of renal haematuria. Nephrotomy is reported not to significantly affect renal function in normal dogs and cats. Indications for nephrotomy associated with the presence of nephroliths may include hydronephrosis and hydroureter associated with renal pelvic obstruction, recurrent infection resistant to conservative treatment, progressive nephrolith enlargement and deterioration of renal function. Pyelolithotomy for calculus removal may only be used when the renal pelvis and the proximal ureter are markedly dilated.